UPAYA UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM REINTEGRASI TENTARA ANAK DI SUDAN SELATAN TAHUN 2018-2021 - Novridiyanti, Dinny; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
South Sudan became a new country that succeeded in holding a referendum on July 9 2011 from Sudan. Before and after gaining independence, the country experienced several conflicts, these conflicts involved child soldiers recruited by the SPLA and the opposition in South Sudan, causing violations of children's rights and war crimes. UNICEF as an organization that has a major role in guaranteeing children's rights takes part in providing reintegration services such as psychosocial support, family reunification and vocational training for former child soldiers who have been successfully released. Therefore, this research aims to determine UNICEF's efforts through the reintegration process for former child soldiers. This research uses the theory of the role and function of international organizations, qualitative research methods with data collection techniques using document analysis. The perspective used is neoliberal institutionalism and uses a systems level of analysis. The research results show UNICEF's efforts to provide reintegration services for former child soldiers in South Sudan, as well as collaborating with various parties to assist the reintegration process and seeing the challenges in the reintegration process. Keywords: Child Soldiers, UNICEF, South Sudan, Reintegrational